Transcriptome and proteome analyses of the molecular mechanisms associated with coix seed nutritional quality in the process of breeding - Huang, Qun; Xu, Meiyu; Zhang, Hailu; He, Dan; Kong, Yuting; Chen, Lei; Song, Hongbo (Food chemistry, 2019)
•Main nutrient content of WC is higher than that of CC.•The proteome and transcriptome of coix during filling stage were analyzed.•A total of 20,039 DEGs and 1,444 DEPs were isolated in WC and CC.•Several metabolism pathways were found to explain the difference of coix seed. In present study, the content of main nutrients in wild coix seed were significantly higher than cultivated coix seed. Transcriptome and proteome were combined to provide new insight of the molecular mechanisms linked to nutritional quality of wild coix seed and cultivated coix seed by RNA sequencing and isobaric tags for relative and absolute quantification techniques. A total of 20,039 genes and 471 proteins exhibited differential expression level in cultivated coix seed when compared with wild coix seed. These genes and proteins revealed that the pathway of flavonoids biosynthesis, starch and sucrose metabolism, lipid metabolism and amino acid metabolism were linked to nutritional quality of coix seed. Our results provided transcriptomics and proteomics information with respect to the molecular mechanisms of nutritional changes of coix seed, identified key genes and proteins that associated with the metabolism and accumulation of nutrients, and helped clarify the mechanisms of nutrient differences.